7 Virtual reality (VR) for the treatment of mental health disorders. Issue 8 (20th July 2020) - Freeman, Daniel
Abstract : Daniel Freeman is an NIHR Research Professor and Professor of Clinical Psychology in the Department of Psychiatry, University of Oxford, a consultant clinical psychologist in Oxford Health NHS Foundation Trust, a fellow of University College Oxford, and leads the Oxford Cognitive Approaches to Psychosis (O-CAP) research group at the University of Oxford. Daniel has been working with virtual reality (VR) since 2001 and is a founder of Oxford VR, a University of Oxford spinout company. Mental health disorders are very common, but far too few people receive the best treatments. Much greater access to the best psychological treatments may be achieved using automated delivery in virtual reality (VR). With virtual reality simulations, individuals can repeatedly experience problematic situations and be taught, via evidence-based psychological treatments, how to overcome difficulties. A key advantage of VR is that individuals know that a computer environment is not real but their minds and bodies behave as if it is real; hence, people will much more easily face difficult situations in VR than in real life and be able to try out new therapeutic strategies. VR treatments can also be made much more engaging and appealing for patients than traditional therapies. A systematic programme of work developing and testing automated VR psychological treatments will be described, with a particular focus on the gameChange (www.gameChangeVR.com) project for schizophrenia.